ANALISIS FRAMING ISU DAHLAN ISKAN PADA SURAT KABAR MANADO POST DAN TRIBUN MANADO EDISI OKTOBER/NOVERMBER 2012 - Gedoan, Junita Trifeni (ACTA DIURNA KOMUNIKASI, 2013)
There is a trend now that all mass media is influenced by interestedness. It is true that all mass media has news construction with theirs ideology themselves. But, journalist of Manado Post and Tribun Manado has to considered the commitment on journalism. It means that journalism need to serve the public interest and devote verity or reality. Keyword : Mass media, interestedness, public interest